Association of Self-Reported Burnout and Protective Factors in Single Institution Resident Physicians - Wood, Elena A. (J Grad Med Educ, 2020)
BACKGROUND: Studies examining mitigating factors associated with residents' experience of burnout have found mixed results; thus the most effective approaches for programs to prevent resident burnout are unclear. OBJECTIVE: We used mixed methods to explore the association of 4 psychological constructs thought to be important protective factors for burnout—grit, resiliency, social support, and psychological flexibility—across a wide variety of residency programs at 1 institution. METHODS:  The explanatory sequential study design included an online survey of previously published scales measuring burnout, grit, resiliency, social support, and psychological flexibility. The survey was sent to 20 residency programs in a single institution during the 2017–2018 academic year. Data were analyzed using descriptive statistics and ordinal logistic regressions to determine the association of protective factors and demographic variables. Interviews with 13 residents were conducted and analyzed deductively and inductively to identify when and how residents employed the protective factors. RESULTS: Among the 268 responders (51% response rate), grit, resiliency, social support, and psychological flexibility were individually inversely associated with burnout level. However, resiliency and relationship status were no longer associated with burnout when all 4 factors were included in the model. Interviews revealed that grit both protects from and contributes to burnout, residents prefer peer support, and they cognitively “step back” when stress is high. CONCLUSIONS: Although many programs and institutions focus on resiliency in wellness programs, there may be other factors to consider, such as grit and equipping students with tools to disengage psychologically when feeling stressed or overwhelmed.